Is cork oak (Quercus suber L.) woodland loss driven by eucalyptus plantation? A case-study in southwestern Portugal - Costa, a; Madeira, M.; Santos Lima, J.; Costa A, Madeira M.; J, Santos Lima (iForest - Biogeosciences and Forestry, 2014)
Mediterranean landscapes with open cork oak (Quercus suber L.) woodlands have recently experienced drastic changes in southwestern Portugal. Changes in agricultural activities, the traditional driver of the economy in this region, led to new land uses such as long-term set aside (shrublands) and eucalyptus plantations. A study was conducted on the oak woodland landscape dynamics over a 50-year period (from 1958 to 2007) in order to assess the effect of different biophysical conditions on landscape spatial changes, and to identify the resilience of lanscape composition to different disturbances (e.g., socio-economic changes and wildfires). Land use changes over two consecutive periods (1958-1995 and 1995-2007) were inferred by spatial analysis of land cover data (aerial photographs) and related to landscape physical attributes (slope and soil type). A transition matrix of four vegetation land-cover classes was obtained, allowing the assessment of the landscape composition changes bewteen the two above periods. Results showed that lansdcape in 1958 was largely occupied by open farmland, with large patches of open oak woodlands on steep slopes surrounding watercourses. Open farmland and shrubland drastically declined from 1958 to 1995, while eucalyptus plantation exhibited a dramatic expansion. Although large areas of cork oak forest turned into eucalyptus plantation, the net loss of oak forest was low and counterbalanced by its increment on former open farmland. The occurrence of a wildfire in 2003 promoted a dramatic decrease in cork oak woodlands, which mostly turned into shrubland. However, shrubland may be considered “safe sites” for ecological succession, ensuring natural cork oak regeneration and the colonization of neighboring areas.
Keywords: agroforestry systems; Eucalyptus Plantations; evergreen oak woodlands; Land Cover; Mediterranean Climate Region; Quercus suber L.

Species richness and similarity of vascular plants in the Spanish dehesas at two spatial scales - Garcia, Jose M; Ponce, Rafael Alonso; Benavides, Raquel; Roig, Sonia (Forest Systems, 2014)
Aims of study: The goals of this paper are to summarize and to compare plant species richness and floristic similarity at two spatial scales; mesohabitat (normal, eutrophic, and oligotrophic dehesas) and dehesa habitat; and to establish guidelines for conserving species diversity in dehesas. Area of study: We considered four dehesa sites in the western Peninsular Spain, located along a climatic and biogeographic gradient from north to south. Main results: Average alpha richness for mesohabitats was 75.6 species, and average alpha richness for dehesa sites was 146.3. Gamma richness assessed for the overall dehesa habitat was 340.0 species. The species richness figures of normal dehesa mesohabitat were significantly lesser than of the eutrophic mesohabitat and lesser than the oligotrophic mesohabitat too. No significant differences were found for species richness among dehesa sites. We have found more dissimilarity at local scale (mesohabitat) than at regional scale (habitat). Finally, the results of the similarity assessment between dehesa sites reflected both climatic and biogeographic gradients. Research highlights: An effective conservation of dehesas must take into account local and regional conditions all along their distribution range for ensuring the conservation of the main vascular plant species assemblages as well as the associated fauna
Keywords: agroforestry systems; alpha richness; climatic and biogeographic range; floristic similarity; gamma richness; mesohabitat; non-parametric estimators

Variation in soil C and microbial functions across tree canopy projection and open grassland microenvironments - Lai, Roberto; Lagomarsino, Alessandra; Ledda, Luigi; Roggero, Pier Paolo (TURKISH JOURNAL OF AGRICULTURE AND FORESTRY, 2014)
Mixtures of grasslands and perennial woody crops or vineyards represent a major source of potential carbon storage or release. Understanding the spatial variability of soil properties in these ecosystems is important in determining soil constraints related to the management of soil resources. The aims of the study were 1) to explore the spatial variability associated to the trees for soil C storage and its components and reactivity; and 2) to assess the similarities between microenvironments in terms of microbial functional diversity. Eight microenvironments characterized by different long-term soil management practices and different positions with respect to woody plant canopy soil vertical projections were selected in a Mediterranean agropastoral system. Four management types were considered: pasture, hay crop, grass-covered vineyard, and tilled vineyard. Soil organic C, microbial biomass, and respiration were measured to assess C storage and dynamics, while functional diversity was determined by means of soil enzyme activities. The results showed that the microenvironmental variation of soil organic C and functional microbial diversity generated by the tree canopies in the wooded grassland can be very relevant for an accurate assessment of soil organic C content and its dynamics. The same was not applicable to vineyards, where the spatial variation of both soil organic C and functional diversity was negligible, independently of the soil management practices. These results suggest that in such systems the microscale spatial variability generated by the trees is worth of further investigation for improving our understanding of the long-term management effects on soil C dynamics.
Keywords: agroforestry systems; carbon mineralization; Enzyme activity; long-term management; Tree effect; vineyards

Litter production in Holm oak trees subjected to different pruning intensities in Mediterranean dehesas - Andivia, Enrique; VÁZQUEZ-PIQUÉ, JAVIER; FERNÁNDEZ, MANUEL; Alejano, Reyes (Agroforestry systems, 2012)
Litterfall is a key process in forests which is sensitive to climatic conditions like precipitation and temperature, and management practices. Therefore, knowledge about litterfall patterns and its associated variables is important for the conservation of Mediterranean ecosystems under conditions of climate change. We aimed to quantify the temporal pattern of litterfall and to investigate the inﬂuence of abiotic variables and pruning on litter production. Litterfall was collected at monthly intervals for 2 years in trees subjected to different pruning intensities in two locations. The effect of pruning, abiotic variables and tree size on litter production was analyzed using a mathematical model. Leaf fall was strongly seasonal with a peak occurring in the wettest month of the year in this area. The variability in leaf fall was mainly related to rainfall and soil water in 2 years and locations. Pruning reduced the amount of litter production during the ﬁrst year following this practice, and might have negative effect on soil fertility and crop productivity in dehesas ecosystems.
Keywords: á agroforestry systems; á litterfall á; agroforestry systems; climate change; climate change á management; litterfall; management; pruning; Quercus ilex; quercus ilex á pruning

Spatial distribution of the soil organic carbon pool in a Holm oak dehesa in Spain - Simón, Nuria; Montes, Fernando; Díaz-Pinés, Eugenio; Benavides, Raquel; Roig, Sonia; Rubio, Agustín (Plant and Soil, 2012)
Aims Dehesas are agroforestry systems characterized by scattered trees among pastures, crops and/or fallows. A study at a Spanish dehesa has been carried out to estimate the spatial distribution of the soil organic carbon stock and to assess the influence of the tree cover. Methods The soil organic carbon stock was estimated from the five uppermost cm of the mineral soil with high spatial resolution at two plots with different grazing intensities. The Universal Kriging technique was used to assess the spatial distribution of the soil organic carbon stocks, using tree coverage within a buffering area as an auxiliary variable. Results A significant positive correlation between tree presence and soil organic carbon stocks up to distances of around 8 m from the trees was found. The tree crown cover within a buffer up to a distance similar to the crown radius around the point absorbed 30 % of the variance in the model for both grazing intensities, but residual variance showed stronger spatial autocorrelation under regular grazing conditions. Conclusions Tree cover increases soil organic carbon stocks, and can be satisfactorily estimated by means of crown parameters. However, other factors are involved in the spatial pattern of the soil organic carbon distribution. Livestock plays an interactive role together
Keywords: agroforestry systems; Soil C; Spatial variance partition; Tree effect; Universal Kriging

Organic C distribution and N mineralization in soil of oak woodlands with improved pastures - Gómez-Rey, Maria Xesús; Garcês, Ana; Madeira, Manuel (Revista de Ciências Agrárias, 2011)
Cork oak woodlands in Portugal are a multipurpose agroforestry system occurring in areas mostly degraded by former cereal crops and overgrazing. The objective of this study was to evaluate the effect of scattered cork oak trees (Quercus suber L.) on soil quality, considering two land use systems: unmanaged pastures and improved pastures. Soil samples were collected in a square grid around scattered cork oak trees to evaluate the spatial variability of soil bulk density and chemical properties. In soil samples taken beneath tree canopy and in the open, net N mineralization was evaluated by aerobic incubations. Also, laboratory incubations were carried out to evaluate the effect of roots (tree or/and herbaceous) and water solutions (bulk precipitation, throughfall or stemflow) on net N mineralization.Contents of organic C, total N and extractable P were increased beneath the tree canopy, and gradually decreased with the increase of distance to the tree trunk. Improved pastures established 26 years ago increased organic C (0.76 kg m-2), total N (0.06 kg m-2) and extractable P (2.70 g m-2) amounts in the 0-10 cm soil layer beneath the tree canopy relatively to those of unmanaged pastures. Net N mineralization was significantly greater (about 2 times) in soils beneath the tree canopy than in those of open areas. N mineralization was unaffected by addition of throughfall or stemflow, while a significant reduction resulted from tree roots addition, this effect being stronger for herbaceous plant roots than for tree roots. Maintenance of tree cover combined with permanent improved pastures should be considered to improve soil quality in oak woodlands of Southern Portugal.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: agroforestry systems; legumes; Mediterranean climate; soil quality.

Contingent Valuation of Woodland-Owner Private Amenities in Spain, Portugal, and California. - Campos, Pablo; Oviedo, Jose L; Caparros, Alejandro; Huntsinger, Lynn; Coelho, Inocencio (Rangeland Ecology & Management, 2009)
Most of the Mediterranean woodlands in Spain, Portugal, and California are managed as agrosilvopastoral enterprises, producing some combination of livestock, wood, cork products, and crops, as well as wildlife habitat and diverse environmental services. Private amenity benefits to landowners have been suggested as an explanation for high land prices and the persistence of such rangeland enterprises despite apparently marginal cash returns. In this study, private amenity values are estimated using a contingent valuation technique in surveys of private woodland owners as part of five case studies, using a design developed to separate landowner amenity income and capital values. Nonindustrial private landowners were asked about the maximum amount of money that they were willing to give up (to pay) before selling their property to invest in more commercially profitable assets, and the proportion of the market price of their woodland that they think is explained by privately consumed amenities. Amenity values were found to be relevant because, in all cases, landowners were willing to pay >€120 · ha−1 · yr−1, at 2002 prices, and attributed > 30% of land market price to amenities. These values represent an amenity profitability rate > 2% in all case studies. The data analysis shows some similarities, but mostly divergences, in the different land-simulated and amenity-simulated markets.
Keywords: agroforestry systems; environmental economics; environmental services; Mediterranean woodlands; private ownership; Stated Preferences

Contingent Valuation of Woodland-Owner Private Amenities in Spain, Portugal, and California. - Campos, Pablo; Oviedo, José L.; Caparros, Alejandro; Huntsinger, Lynn; Coelho, Inocencio (Rangeland Ecology & Management, 2009)
Most of the Mediterranean woodlands in Spain, Portugal, and California are managed as agrosilvopastoral enterprises, producing some combination of livestock, wood, cork products, and crops, as well as wildlife habitat and diverse environmental services. Private amenity benefits to landowners have been suggested as an explanation for high land prices and the persistence of such rangeland enterprises despite apparently marginal cash returns. In this study, private amenity values are estimated using a contingent valuation technique in surveys of private woodland owners as part of five case studies, using a design developed to separate landowner amenity income and capital values. Nonindustrial private landowners were asked about the maximum amount of money that they were willing to give up (to pay) before selling their property to invest in more commercially profitable assets, and the proportion of the market price of their woodland that they think is explained by privately consumed amenities. Amenity values were found to be relevant because, in all cases, landowners were willing to pay > €120 · ha−1 · yr−1, at 2002 prices, and attributed > 30% of land market price to amenities. These values represent an amenity profitability rate > 2% in all case studies. The data analysis shows some similarities, but mostly divergences, in the different land-simulated and amenity-simulated markets.
Keywords: agroforestry systems; environmental economics; environmental services; Mediterranean woodlands; private ownership; Stated Preferences

Analisis de los recursos de pastoreo aportados por el medio en dos Dehesas caracteristicas del sur de la provincia de Badajoz (España) - Sánchez, M Escribano; García, F Pulido (Archivos de zootecnia, 1994)
En este trabajo se analizan los recursos de pastoreo en dos explotaciones características de dehesa de Extremadura en el año 1992, Desde el punto de vista de la evaluación técnica, se observa que el sistema cubre, con recursos propios, entre el 54 y el 56 p.100 de las necesidades de la ganadería doméstica en el año de estudio, que se caracterizó por una climatología adversa, Por otro lado, los recursos de pastoreo suponen una de las principales utilidades económicas del sistema dehesa, cuya efectividad económica dependerá de la posibilidad de sustitución y del precio de mercado de las materias primas energéticas comerciales.
Keywords: agroforestry systems; Economic analysis; Extensive systems; natural resources; pastures

Land degradation in Mediterranean Europe: can agroforestry be a part of the solution? A prospective review - Houérou, H N (Agroforestry Systems, 1993)
Vegetation and land degradation, although less acute than in the Southern Medi- terranean Basin, is still widespread in the North. Degradation results from various kinds of mismanagement of the land. Wildfires, for instance, favoured by ungrazing, play an increas- ingly important role as the mean area annually burnt shifted from an average 200,000 ha in the 1960's to over 600,000 ha in the 1980's. These put a heavy burden on the states and on local communities that amounted to an annual average one billion ECUs (USS 1.2 billion) in the 1980's. The causes and processes of land and vegetation degradation are analysed in the light of the changes in land-use over the past 25 years, as shown in the official statistical data. Forest and shrubland areas are expanding while farmland is shrinking by nearly 1% per annum. An analysis of the foreseeable situation in the early years of the twenty-first century is attempted on the basis of the likely evolution of the EEC agricultural policy. Some guidelines are proposed for sound ecological management of the Northern Mediterranean land and vegeta- tion. These include the introduction or expansion of agroforestry systems with multiple-use of the land to develop tourism, wildlife, hunting and sports, combined with extensive grazing of livestock and game and timber production from elite clones of selected high yielding or highly valued species. Eight to ten million hectares, at present devoted to cereal cropping (i.e. about 50% of the cereal-cropping hectarage), will have to be reconverted to other activities. By 1995, the EEC cereal prices will have to drop in line with the world market, as a result of the recent evolution of the EEC Communal Agricultural Policy (CAP). The warranted EEC cereal prices are at present about 40% above that of the world market. The reconversion of this cereal land to other activities could combine low-input mixed agroforestry systems with extensive livestock and game husbandry, high value timber, tourism and various amenities. These should include forage-shrubs plantations in a strategy which combines inexpensive, albeit nutritionally balanced, ruminant diets with erosion control and the overall uplift of natural land fertility and productivity.
Keywords: agroforestry systems; fodder shrubs; Mediterranean basin; multipurpose production systems; range management; sylvo-pastoralism